Historical-Political Reflection on the Movement in the Post-Soviet Space (Czech Journal of International Relations, 1997)
The USSR was disintegrating only recently. All of a sudden and unexpectedly for the majority of its population, in which the feeling of completeness and irreversibility of the disintegration or the natural course and permanence of the current state formations and borders has not yet taken root. The post-Soviet space remains unstable. In almost every republic, there are separatist movements or self-proclaimed illegal states, and at the same time various integration ideas and initiatives are highlighted. The perspective that the space will acquire a stable form is remote. It is hard to imagine that twenty years from now the same states as today will be united in it.The political volatility of the post-Soviet space and the uncertainty of thoughts and feelings arising in connection with its fate are two sides of the same coin. In the years 1989-1991, anti-Soviet sentiments dominated. Various anti-imperial ideas and phrases were plastered on the pages of newspapers, while no one thought about their incoherence and illogicality. The idea of ​​republican sovereignty co-existed peacefully with the idea of ​​the right of ethnic groups to their own territorial independence. Dudayev was perceived as the leader of the Chechen revolution and the hero of the national liberation movement. The demand for the weakening, even liquidation of the center stood in counterpoint to the insistence that the same center take away Karabakh from Azerbaijan and transfer it from its power to Armenia. In Russia and in all the republics, budgets were calculated to the last detail, who loses because it remains part of Russia, how one side exploits the other, howthey would be fine living alone. The strength of anti-union sentiments made it possible to ignore the contradictions and unseriousness of similar projects and concepts.